Institutionalist versus distortionist views of labor market reforms: An investigation into the post-liberalized manufacturing sector in India - Kumar Bhandari, Anup; Sudarsan, Arun (Universidad ESAN. ESAN Ediciones, 2016)
Labor regulation and employment relation has been investigated in India in light of the seminal work ofBesley and Burgess (2004), considering formal sector manufacturing employment as the explained vari-able. Empirical findings support, although not very strongly, the institutionalist view, i.e., pro-workeramendment in labour laws induces employment. Among the other factors, real wage rate has significantnegative effect on employment, whereas that for real per capita developmental capital expenditure, percapita electricity generation capacity and real per capita net state domestic product is significant positive.However, effect of per capita real developmental revenue expenditure is inconclusive. In other words,although it improves employability of workers through their human capital improvement, which is prob-ably met up at the cost of worsening overall infrastructural development, through reducing correspondingcapital expenditure! Supporting evidence has also been provided favoring this conjecture.

La normativa y la regulación laboral se han investigado en la India a raíz del trabajo original de Besleyy Burguess (2004), tomando como variable el empleo formal en el sector manufacturero. Los hallazgosempíricos respaldan, aunque no rotundamente, la visión institucionalista, es decir, que la enmienda afavor del trabajador en la legislación laboral fomenta el empleo. Entre otros factores, la tasa de salarioreal tiene un impacto significativamente negativo en el empleo, mientras que para la inversión de capitalde desarrollo per cápita, la capacidad de generación de electricidad per cápita y el producto interno essignificativamente positiva. No obstante, el efecto del costo de los ingresos del desarrollo real per cápitano es concluyente. En otras palabras, si bien esto favorezca la inserción laboral de los trabajadores con unamejora del capital humano, probablemente se consiga a costa de empeorar el desarrollo de infraestructuraal reducir la inversión en capital correspondiente. Se presenta evidencia que avala esta conjetura.
Keywords: Labor regulation; Formal sector; Regulación laboral; Manufacturing employment; Sector formal; Empleo manufacturero; Liberalization; Liberalización; https://purl.org/pe-repo/ocde/ford#5.02.04